Playing Fair: How “Alternative” Fair Trade and Organic Quinoa Markets in Bolivia Affect Producer Livelihoods - Lunardi, Ode (Université d'Ottawa / University of Ottawa, 2017)
This thesis seeks to analyze the “alternative” nature of organic and fair trade markets and whether they are truly challenging the neoliberal food system, using the case of Bolivian quinoa, traditionally a subsistence crop, to analyze the effects on producer livelihoods. Field research, conducted from April until August 2015, focuses on two areas in the Altiplano sur: the small community of Rodeo and the town of Salinas de Garcí Mendoza. The study uses a political ecology and historical materialist theoretical framework and an ethnographically oriented livelihoods approach, in order to better weave the macro-processes of power to producers’ struggles over their livelihoods. Though organic and fair trade markets are by no means revolutionizing quinoa production or relationships of production in Bolivia, they are providing better terms of trade for producers and allowing them to maintain more traditional, small scale modes of production and community levels of organization. In addition, field research helped facilitate a critical discussion about the challenges and opportunities afforded by these alternatives, talking directly to producers and tying their local difficulties to larger, structural realities: a humble first step in problematizing a common lived struggle.
Keywords: quinoa; political ecology; livelihoods; Bolivia; organic; fair trade; power; food security; globalization; Altiplano sur